Mixed-gas CH(4)/CO(2)/CO detection based on linear variable optical filter and thermopile detector array - Zhang, Shaoda (Nanoscale Res Lett, 2019)
This paper presents the design, fabrication, and characterization of a middle-infrared (MIR) linear variable optical filter (LVOF) and thermopile detectors that will be used in a miniaturized mixed gas detector for CH(4)/CO(2)/CO measurement. The LVOF was designed as a tapered-cavity Fabry-Pérot optical filter, which can transform the MIR continuous spectrum into multiple narrow band-pass spectra with peak wavelength in linear variation. Multi-layer dielectric structures were used to fabricate the Bragg reflectors on the both sides of tapered cavity as well as the antireflective film combined with the function of out-of-band rejection. The uncooled thermopile detectors were designed and fabricated as a multiple-thermocouple suspension structure using micro-electro-mechanical system technology. Experimentally, the LVOF exhibits a mean full-width-at-half-maximum of 400 nm and mean peak transmittance of 70% at the wavelength range of 2.3~5 μm. The thermopile detectors exhibit a responsivity of 146 μV/°C at the condition of room temperature. It is demonstrated that the detectors can achieve the quantification and identification of CH(4)/CO(2)/CO mixed gas.